The mesoscale structure of a polar low: airborne lidar measurements and simulations - Wagner, J.S.; Gohm, A.; Dörnbrack, Andreas; Schäfler, Andreas (Quarterly Journal of the Royal Meteorological Society, 2011)
The mesoscale structure of a mature polar low was studied on the basis of high-resolution airborne measurements and numerical modelling. A polar low was measured by light detection and ranging (lidar) and dropsonde observations over the Norwegian Sea on 3 and 4 March 2008. Lidar observations provided cross-sections of water-vapour mixing ratio, backscatter ratio and horizontal wind speed around the polar low and through its centre. Mesoscale structures, such as shallow convection in a cold-air outbreak, a dry intrusion in the eye-like centre of the cyclone and deep convection surrounding it could be identified. Numerical simulations were performed with the European Centre for Medium-Range Weather Forecasts (ECMWF) Integrated Forecast System (IFS) and a high-resolution, polar version of the Weather Research and Forecasting (WRF) model. WRF simulations reproduced these structures and showed that the polar low had a warm, upper-level core with descending motions. The eye-like centre had a diameter of about 100Ã¢ÂÂ150 km and was characterized by rather stable stratification, horizontally constant potential temperatures and calm winds. Beyond the centre, wind speeds increased rapidly. The observed radial wind and temperature profiles support previous idealized simulations. Several WRF sensitivity tests showed the influence of the initialization time and sensible and latent heat fluxes from the surface on the simulated polar-low development. The polar-low simulations were more accurate in runs starting at the mature stage. Heat fluxes from the surface were important for the polar-low energetics, especially at the final stages.